Conservation Approaches of Patina Formation on Marble and Travertine Surfaces in the Archaeological Sites - Badur, Fulya; Böke, Hasan; Yalçın, Şerife (Izmir Institute of Technology, 2017)
Patina, which is formed on the stone surfaces of historical buildings and monuments as a result of aging, is considered as a value of the building in the conservation of cultural heritage studies. It should be conserved on calcareous stone surfaces whether or not it represents protective characteristics, since it provides information about previous times. Within this respect, the determination of mineralogical composition, and microstructural and chemical characteristics of patina are critical for the conservation decisions. The aim of this study is to determine the characteristics of yellow patina formation on marble and yellow travertine surfaces to constitute a conservation approach in the archaeological sites. In this study, XRD, FT-IR, SEM-EDX, LIBS and TGA were used to determine the characteristics of yellow patina formation on marble and yellow travertine surfaces in Aizanoi, Aphrodisias, Sardes and Hierapolis. Analysis results indicated that yellow patina is mainly composed of calcium oxalate (whewellite or weddelite) minerals. CaO, MgO, Al2O3, SiO2, P2O5, K2O, SO3, FeO and Na2O were observed on the chemical analyses of the same samples. The results of LIBS and SEM-EDX showed that Ca increases, and other elements decrease from surface to the sound inner parts of the stone due to calcium oxalate and gypsum precipitation and clay deposition on the surfaces. The calcium oxalate patina forms a homogeneous film layer on calcite crystals. It is most likely formed by the reaction of calcite and oxalic acid produced by the biological formations on stone surfaces. It is colorless in original. The yellow color may be related with the FeO and clay deposition on the stone surfaces. The outcomes of the study proved the presence of a protective yellow patina formation on yellow travertine surfaces against the weathering effects of water which cannot be distinguished by naked eye. This patina presents same characteristics with the yellow patina on marble surfaces which should be conserved. The results of this study show that the determination of yellow patina is critical to keep irreversible cleaning interventions away from surfaces especially for the monuments that yellow travertine is used as building materials.

Tarihi bina ve anıtların taş yüzeylerinde yaşlanma sonucu meydana gelen patina, kültürel mirasın korunması ile ilgili çalışmalarda yapının değeri olarak ele alınmaktadır. Dolayısıyla, kalkerli taş yüzeylerinde koruyucu özelliği olup olmadığına bakılmaksızın korunması gerekmektedir. Zira patina, geçmiş dönemler ile ilgili bilgiler taşımaktadır. Bu açıdan patinanın mineralojik kompozisyonu ile kimyasal ve mikro yapısal özelliklerinin belirlenmesi koruma kararlarının oluşturulmasında önemlidir. Bu çalışmanın amacı mermer ve sarı traverten yüzeylerindeki sarı patinanın özelliklerinin arkeolojik alanlarda koruma yaklaşımlarının oluşturulması için belirlenmesidir. Bu çalışmada, Aizanoi, Aphrodisias, Sardis ve Hierapolis’te bulunan mermer ve sarı traverten yüzeylerinde oluşan sarı patina oluşumlarının özelliklerinin belirlenmesi için XRD, FT-IR, SEM-EDS, LIBS ve TGA kullanılmıştır. Analiz sonuçları, sarı patinanın çoğunlukla kalsiyum oksalat (vedelit veya vevelit) minerallerinden oluştuğunu göstermektedir. Aynı örneklerin kimyasal analiz sonuçlarında CaO, MgO, Al2O3, SiO2, P2O5, K2O, SO3, FeO ve Na2O elementleri bulunmuştur. LIBS ve SEM-EDX sonuçlarında, yüzeyde biriken kalsiyum oksalat, alçı ve kil minerallerinden dolayı yüzeyden sağlam iç kısımlara gidildikçe Ca oranının arttığı ve diğer elementlerin azaldığı görülmüştür. Kalsiyum oksalat kalsit kristallerinin üzerinde homojen bir film tabakası oluşturmaktadır. Bunun kalsit ve taş yüzeylerindeki biyolojik oluşumların ürettiği oksalik asitin reaksiyonu sonucu oluştuğu düşünülmektedir. Kalsiyum oksalat renksizdir. Kalsiyum oksalat patinasının sarı rengi taş yüzeylerinde biriken demir oksit ve kil minerallerinden kaynaklanabilir. Elde edilen bilgiler, traverten yüzeylerinde çıplak gözle ayırt edilemeyen suya karşı koruyucu bir sarı tabakanın varlığını ispatlamaktadır. Bu patina, mermer yüzeylerinde oluşan ve korunması gereken sarı kalsiyum oksalat tabakası ile aynı niteliktedir. Bu çalışmanın sonuçları, sarı kalsiyum oksalat patinasının tespitinin, özellikle sarı traverten kullanılan tarihi yapılarda geri dönüşü olmayan temizleme uygulamalarından kaçınılması açısından önemli olduğunu göstermektedir.
Arkeolojik Alanlarda Bulunan Mermer ve Traverter Yüzeylerindeki Patina Oluşumlarının Koruma Yaklaşımları
Thesis (Doctoral)--İzmir Institute of Technology, Architecture, İzmir, 2017
Full text release delayed at author's request until 2020.08.17
Includes bibliographical references (leaves: 119-125)
Text in English; Abstract: Turkish and English
Keywords: Patina; Conservation and restoration; Historical buildings; Archaeological site; Mineralogical composition